The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Environmental Hazards and Neurodevelopment 2015
DOI: 10.1201/b18030-10
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Year Neurodevelopmental Scores and Prenatal Exposure to Chlorpyrifos, a Common Agricultural Pesticide

Abstract: Background: Autism Spectrum Disorders (ASD) is a syndrome with a number of etiologies and different mechanisms that lead to abnormal development. The identification of autism biomarkers in patients with different degrees of clinical presentation (i.e., mild, moderate and severe) will give greater insight into the pathogenesis of this disease and will enable effective early diagnostic strategies and treatments for this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
2
Order By: Relevance
“…This suggests that individuals with ASDs may have a decreased ability to eliminate heavy metals from the body due to a genetic etiology (Kern et al, 2007). Furthermore, individuals with ASDs have impairments in detoxification and have lower levels of antioxidants, such as glutathione-s-transferase and vitamin E (Alabdali et al, 2014). This may cause these individuals to be more susceptible to the accumulation of toxic metals such as mercury and lead.…”
Section: Air Pollution and Heavy Metalsmentioning
confidence: 99%
“…This suggests that individuals with ASDs may have a decreased ability to eliminate heavy metals from the body due to a genetic etiology (Kern et al, 2007). Furthermore, individuals with ASDs have impairments in detoxification and have lower levels of antioxidants, such as glutathione-s-transferase and vitamin E (Alabdali et al, 2014). This may cause these individuals to be more susceptible to the accumulation of toxic metals such as mercury and lead.…”
Section: Air Pollution and Heavy Metalsmentioning
confidence: 99%
“…In considering the results observed in this study from a mechanistic point of view for ASD etiology, it was hypothesized that persons with oxidative stress and transsulfuration abnormalities would be a greater risk of developing an ASD following environmental toxicant exposures (Alabdali, Al‐Ayadhi, & El‐Ansary, ). Specifically, it was suggested that limited thiol availability, abnormal sulfation chemistry, and decreased glutathione reserve capacity in children would result in such persons having greater accumulation of environmental toxicants in the brain leading to neuronal damage, and, ultimately, an ASD diagnosis (Kern et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alabdali et al [10], Biochemiker des Science College in Riad, untersuchten die Konzentration von 2 Schwermetallen, Blei und Quecksilber, in Erythrozyten von Kindern mit ASS sowie die Plasmaspiegel von Glutathion-S-Transferase (GST) und Vitamin E. Die Patienten mit ASS hatten deutlich erhöhte Quecksilber-und Bleiwerte sowie abgesenkte GST-und Vitamin-E-Werte. Blei wird z.…”
Section: Umweltgifte: Aluminium Blei Quecksilberunclassified
“…B. über Kohleheizung oder Feinstaub von Kohlekraftwerken, bleihaltige Autoabgase, Farbe und Haarfärbemitteln aufgenommen [9]. Die Autoren [10] sehen darin einen deutlichen Hinweis, dass Schwermetallablagerungen und möglicherweise Schwierigkeiten mit der körpereigenen Ent-giftung eine wichtige Rolle in der Ätiologie von ASS spielen.…”
Section: Umweltgifte: Aluminium Blei Quecksilberunclassified